Parameterestimation of damped compound pendulum using firefly algorithm - Mohamad Izzat Kamal (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
When a problem is large or difficult to solve, computer are often used to find the solution. But when the problem becomes too large, traditional methods of finding the answer may not be enough. It is in turning to nature that inspiration can be found to solve these difficult problems. Artifical intelligence seek to emulate creatures and processes found in nature, and turn their techniques for solving a problem into an algorithm.